Metastatic neck node: a straying journey to diagnosis - Galagali, J. R.; Singh, Roohie (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Squamous cell carcinoma of lung is most commonly associated with smoking. Its metastasis to contralateral neck node as the first presenting symptom is very rare. Tuberculosis (TB) and cancer of lung have causal relationship. There may also be coexistence of another neoplasm around the time of diagnosis of primary neoplasm. We present a case report of an 80 years old man who presented with a contralateral metastatic neck node. He was diagnosed to have coexistent lung cancer and pulmonary TB. In this journey towards diagnosis, the findings suggestive of tubercular larynx might have been a sequel of pulmonary TB.